Recent progress in benzimidazole and quinoxaline dyes based on dye-sensitized solar cell: a comprehensive overview - Nassar, Maadh F.; Abdulmalek, Emilia; Ismail, Mohd F.; Alang Ahmad, Shahrul Ainliah; Abdulkreem-Alsultan, G. (Springer, 2023)
Due to their benefits like low cost, simple processing, mass production, and effective conversion of solar energy into electrical energy, dye-sensitized solar cell (DSSC) devices have garnered a lot of attention in the scientific community over the past few years. It is well known that the architecture and composition of the photosensitizers play a key role in improving the functioning of the DSSC. Among the many types of fundamental units, benzimidazole and quinoxaline architectures have been particularly effective in the fabrication of DSSCs due to their extreme flexibility. The main aim of this review discussion is to focus on the application of benzimidazole and quinoxaline dyes in DSSC. Incorporating benzimidazole and quinoxaline units into dyes with a D−π−A arrangement showed enhance light-harvesting, optoelectronic, electrochemical, and photovoltaic capabilities while preventing electron recombination processes. Moreover, the maximum efficiency of benzimidazole when incorporated as ancillary donor, main donor, acceptor, n-spacer and ligand have been demonstrated. Therefore, the performance of quinoxaline dyes based on internal acceptor with one donor at (5, 8), double donor at (5, 8), double donor at (2, 3) positions as well as fused quinoxaline-Indolo based donor unit have been received a particular attention in this work. This comparative and comprehensive overview provides up-to-date knowledge and may serve as a lighthouse for young aspiring researchers interested in exploring molecular engineering potential for creating and synthesizing more efficient exotic materials for solar cells.